2012
DOI: 10.1246/cl.2012.766
|View full text |Cite
|
Sign up to set email alerts
|

Iodide-promoted Deselenylation of β-Chloro- and β-Oxyselenides to Form Alkenes and Selenenyl Iodides

Abstract: Deselenylation reaction of β-chloro- and β-oxyselenides proceeded efficiently by treatment with tetrabutylammonium iodide (TBAI) to afford alkenes in good yields. It was established that selenenyl iodides were formed in these reactions. Catalytic transformation of β-chloro- and β-oxyselenides to alkenes was also developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…These changes were found to be reversible, indicating the existence of an equilibrium, as shown in eqn (1), which favors the reactants 1a and 2a around room temperature. These results are in sharp contrast to the reactions of RSeCl or RSeBr with olefins, in which the equilibrium strongly favors the corresponding adducts, 27,29 and are rather similar to the addition of I 2 to olefins. 30 To clarify the thermodynamics of the addition of selenenyl iodide 1a to olefin 2a , variable-temperature (VT) 1 H NMR experiments were conducted in CDCl 3 , in which no compounds other than 1a , 2a , and 3a were observed (Fig.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…These changes were found to be reversible, indicating the existence of an equilibrium, as shown in eqn (1), which favors the reactants 1a and 2a around room temperature. These results are in sharp contrast to the reactions of RSeCl or RSeBr with olefins, in which the equilibrium strongly favors the corresponding adducts, 27,29 and are rather similar to the addition of I 2 to olefins. 30 To clarify the thermodynamics of the addition of selenenyl iodide 1a to olefin 2a , variable-temperature (VT) 1 H NMR experiments were conducted in CDCl 3 , in which no compounds other than 1a , 2a , and 3a were observed (Fig.…”
Section: Resultscontrasting
confidence: 80%
“…26 We also reported that the selenenyl iodide has an intrinsically high thermal stability as long as the diselenide formation is sterically prevented, 25 c ,25 d and that the high affinity between selenium and iodine can be applied to iodide-promoted deselenylation reactions. 27 Due to the reliable stability of 1a , this compound is expected to be useful as a benchmark compound to evaluate the chemical reactivity of a selenenyl iodide in various reactions. Herein, we report the characteristic thermodynamics of the reaction of a selenenyl iodide with an olefin and the development of the efficient oxyselenation and aminoselenation of olefins using the isolable selenenyl iodide 1a .…”
Section: Introductionmentioning
confidence: 99%
“…[13] Astonishingly, this addition process to the alkene seems to be "reversible" in the presence of other halide anions, such as iodide, so that PhSeI and Cl À are formed while the alkene is regenerated, as was reported by Goto (Scheme 3). [14] Therefore, iodide anions will lead to the reverse process and cannot be applied as low-redox potential mediator to oxidise the envisaged Se(II) intermediate 6 (Scheme 3) to a Se(IV) species 5. This is believed to be needed for the second nucleophilic substitution reaction (compare Scheme 2, transformation of 5 in step D).…”
mentioning
confidence: 99%
“…This proposed mechanism is strongly supported by a report from Goto and co-workers, in which they show that an iodide ion promotes deselenylative alkene formation from β-chloro-and β-oxyselenides via a seleniranium intermediate. 14 On the basis of these considerations, the structures corresponding to the other peaks appearing between 10 and 15 min in the HPLC profile of the trimer and tetramer synthesis (Figure 2A) were all determined ( Figure S8, Supporting Information).…”
mentioning
confidence: 99%
“…This proposed mechanism is strongly supported by a report from Goto and co-workers, in which they show that an iodide ion promotes deselenylative alkene formation from β-chloroand β-oxyselenides via a seleniranium intermediate. 14 On the basis of these considerations, the structures corresponding to the other peaks appearing between 10 and 15 min in the HPLC profile of the trimer and tetramer synthesis (Figure 2A) were all determined (Figure S8, Supporting Information). As described above, oxidation using I 2 induced an unexpected strand break in the growing ON, which resulted in an insufficient yield of the desired ON.…”
mentioning
confidence: 99%